Electronic Processes in Cd[In.sub.2][Te.sub.4] Crystals - Grushka, O.G; Chupyra, S.M; Bilichuk, S.V; Parfenyuk, O.A (Semiconductors (Woodbury, N.Y.), 2018)
The results of investigations of electrical, optical, and photoelectric properties of Cd[In.sub.2][Te.sub.4] crystals, which were grown by the Bridgman method are presented. It is shown that electrical conductivity is determined mainly by electrons with the effective mass [m.sub.n] = 0.44[m.sub.0] and the mobility 120-140 [cm.sup.2]/(V s), which weakly depends on temperature. Cd[In.sub.2][Te.sub.4] behaves as a partially compensated semiconductor with the donor-center ionization energy [E.sub.d] = 0.38 eV and the compensation level K = [N.sub.a]/[N.sub.d] = 0.36. The absorption-coefficient spectra at the energy hv < [E.sub.g] = 1.27 eV are subject to the Urbach rule with a typical energy of 18-25 meV. The photoconductivity depends on the sample thickness. The diffusion length, the charge-carrier lifetime, and the surface-recombination rate are determined from the photoconductivity spectra.